Patient and clinician experience of a serious illness conversation guide in oncology: A descriptive analysis. (4th May 2020) - Paladino, Joanna; Koritsanszky, Luca; Nisotel, Lauren; Neville, Bridget A.; Miller, Kate; Sanders, Justin; Benjamin, Evan; Fromme, Erik; Block, Susan; Bernacki, Rachelle
Abstract: Background/objective: Oncology guidelines recommend earlier communication with patients about prognosis and goals‐of‐care in serious illness. However, current evidence leaves gaps in our understanding of the experience of these conversations. This analysis evaluates the patient and clinician experience of a conversation using a Serious Illness Conversation Guide (SICG). Design/setting: Secondary analysis from a cluster‐randomized clinical trial in a northeastern cancer center. Participants: Physicians, advanced practice clinicians, and patients with advanced cancer who received the intervention. Intervention: SICG, clinician training, systems‐changes. Main outcomes and measures: The patient questionnaire assessed perceptions of the conversation and impact on anxiety, hopefulness, peacefulness, sense of control over medical decisions, closeness with their clinician, and behaviors. The clinician questionnaire assessed feasibility, acceptability, and impact on satisfaction in their role. Results: We enrolled 54 clinicians and 163 patients; 41 clinicians and 118 patients had a SICG discussion. Most patients described the conversation as worthwhile (79%) and reported no change or improvement in their sense of peacefulness, hopefulness, and anxiety (on average 79%); 56% reported feeling closer with their clinician. Qualitative patient data described positive behavior changes, including enhanced planning for future care and increased focus on personal priorities. Nearly 90% of clinicians agreed that the SICG facilitated timely, effective conversations, and 70% reported increased satisfaction in their role. Conclusion: Conversations using a SICG were feasible, acceptable, and were associated with positive experiences for both patients and clinicians in oncology in ways that align with national recommendations for serious illness communication. This trial is registered at ClinicalTrials.gov: NCT01786811 https://clinicaltrials.gov/ct2/show/NCT01786811 . Abstract : This descriptive analysis reports the patient and clinician experience of a structured conversation about patients' values, goals, prognosis, and care preferences in the outpatient setting in oncology. Conversations using the Serious Illness Conversation Guide were feasible, acceptable, and were associated with positive experiences for both patients with advanced cancer and oncology clinicians in ways that align with national recommendations for serious illness communication.